Application of the modified RIAM method in assessing the environmental impact of municipal solid waste management scenarios (A case study) - Mehdi Ghanbarzadeh Lak; Mir Javad Gheybi; Sajjad Chehreghani (Heliyon)
The rapid impact assessment matrix (RIAM) is a widely utilized tool for evaluating environmental impacts in municipal solid waste management. However, the traditional RIAM (T-RIAM) method includes ambiguities in its scoring classification, which can hinder decision-making accuracy. This study introduces a modified RIAM approach, enhancing classification precision by refining impact categories, making it particularly valuable for projects constrained by time and resources. Using the Nazlou landfill in Urmia, Iran, as a case study, two waste management scenarios were assessed: (1) constructing a new landfill cell with leachate treatment facilities and (2) adding a composting plant to divert organic waste. The second scenario was identified as the optimal choice due to its positive environmental impacts across physical-chemical, biological-ecological, and socio-cultural domains, as well as its high public acceptance. Under the proposed classification scheme, the ''+E,'' ''+D,'' and ''–C″ impacts for this scenario decreased from 3, 7, and 3 (as per T-RIAM) to 2, 2, and 0, respectively. The refined scoring system allowed sharper differentiation, with only the most significant impacts classified in ''+E″ or ''–E″ categories, facilitating clearer decision-making compared to T-RIAM. Additionally, the streamlined classification approach reduces the need for extensive data inputs, making the modified RIAM an efficient alternative to resource-intensive methods like life cycle assessment for preliminary evaluations. Beyond waste management, the modified RIAM framework has potential applications in addressing broader environmental challenges, including water resource management, air quality assessment, and infrastructure planning, offering versatile utility for municipal decision-making.